The EU Global Gateway in Africa : Aligning External EU Policies Within a Strategic Resilience Framework in a Competitive Geopolitical Landscape - Brabenec, Patrik; Votoupalová, Markéta; Přikryl, Pavel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis critically examines the European Union’s Global Gateway (GG) Initiative in Africa as a geoeconomic tool aligned with the EU’s broader industrial and strategic policies. Through a dual-metric framework that assesses both geostrategic alignment and declared adherence to EU values, the research investigates flagship GG projects—particularly in green hydrogen and critical raw materials. It covers Namibia, Morocco, Egypt, and Mauritania, alongside infrastructure developments like the Lobito Corridor with DRC, Zambia and Angola. Drawing from geoeconomic theory, energy security literature, and official EU policy documents, the study positions the GG not merely as a development aid mechanism, but as a strategy to enhance EU resilience, reduce dependencies, and secure supply chains vital for the green transition. The thesis employs a qualitative case study approach, supported by quantitative projections and project analyses, to evaluate the extent to which these initiatives reflect EU industrial ambitions and its stated principles of sustainable, equitable partnerships. Findings suggest a growing willingness of the EU to act geostrategically and to address vulnerabilities.
Vedoucí práce: Markéta Votoupalová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses